Desenvolvimento de metodologias analíticas usando FIA com detecção amperométrica: análise de dopamina, ácido ascórbico e ácido úrico - Gimenes, Denise Tofanello (2009)
In the present work a simple, sensitive and selective method for determination of compounds of pharmaceutical and biological interest was investigated. The studies were addressed for analysis of the following analytes: (1) dopamine (DA) in the presence of high concentrations of ascorbic acid (AA); (2) dopamine in the presence of ascorbic and uric acid (UA) and (3) ascorbic and uric acid simultaneously. In all cases, Flow Injection Analysis (FIA) with Multiple Pulse Amperometry (MPA) technique and glassy carbon as work electrode (without chemical modification) were used. Initially, the electrochemical behavior of the analytes in sulfuric acid medium (0.20 mol L-1) was evaluated. The choice of this electrolyte was due to the fact that the chemical reaction between the o-dopaminoquinone (o-DQ) and AA in this condition is very slow. For dopamine analysis, in the presence of high concentrations of ascorbic acid, the following potential pulses in function of the time were used: (a) +0.8V / 700ms : simultaneous oxidation of DA and AA; (b) +0.35V / 30ms: indirect determination of DA through the reduction of o-DQ generated in the previous potential pulse; (c) 0.0V / 500ms: cleaning or regeneration of the electrode surface. Repeatability tests presented a RSD of 1.2% (n=24), which demonstrates a good performance of the proposed method in relation to the technique efficiency to avoid electrode surface contamination. The linear range for DA analysis in the presence of 1 mmol L-1 of ascorbic acid was found to be from 1,0 to 100,0 μmol L-1. The correlation coefficient was calculated as R=0.9988. The detection and quantification limits were 50 and 170 nmol L-1, respectively. Recovery studies were carried out by adding standard DA to a pharmaceutical sample. Good recovery values were obtained (96.3%). For DA determination in the presence of AA and UA, it was necessary to change the oxidation potential pulse (generation of o-DQ) from 0.80 V to +0.65V (the UA oxidation does not occur). The same reduction and cleaning potential pulses were used and only the time of application for the cleaning potential pulse needed to be increased (800ms). Repeatability studies for DA analysis in the presence of AA and UA presented good results, with RSD calculated in 0.25% for 15 successive injections of solution containing simultaneously AA (1.0 mmol L-1),UA (0.50 m mol L-1) and DA (50.0 μmol L-1). In this last case, the linear range for DA analysis was also between 1.0 to 100.0 μmol L-1, with correlation coefficient, detection and quantification limits calculated, respectively, as 0.998, 11 nmol L-1 and 37 nmol L-1. Simultaneous analysis of AA and UA were carried out using the following sequence of potential pulses: a) +0.6V / 100ms: oxidation and quantification of ascorbic acid; b) +0.8V / 100ms: oxidation of AA and UA; c) +0.1V / 30ms: reduction of the oxidation product of UA and respective quantification; d) 0.0V/ 1s: cleaning and/or regeneration of the electrode surface. In the simultaneous analysis of AA and UA, the RSD for successive injections (n=25) of a solution containing AA+UA (100.0 and 200.0 μmol L-1) was calculated in 0.3 and 0.6 %, respectively. The analytical curve presented linear behavior (current vs concentration) between 100.0 to 300.0 and 50.0 to 150.0 μmol L-1 for AA and UA, respectively. Based on these results, other parameters were calculated, respectively, for AA and AU analysis: correlation coefficients (R = 0.997 and 0.995), detection limits (82 and 273 nmol L-1) and quantification limits (169 and 563 nmol L-1).